An Investigation of Environmental Inequality in a Metropolitan Area - Zohre Sadat Pourtaghi; Farhad Nejadkoorki; Mohsen Asadi- Lari; Esmaeil Khedmati Morasae; Zahra Nasrollahi (Shahid Sadoughi University of Medical Sciences, 2014)
Introduction: Inequalities in urban environment are a significant concern. Socioeconomic level plays an important role in these inequalities. Inequality in environmental hazards is recognized as potential determinants of health disparities. Materials & Methods: In this study, we used individual and cumulative environmental hazard inequality indices to compare the inequality among 379 neighborhoods in the city. Inequality indices were calculated based on unequal shares of environmental hazards for socioeconomic status (SES). The hazards include ambient concentrations of PM10 and NO2 in 2011. Results: Results revealed that inequalities from cumulative hazards (additive and multiplicative) and individual PM10 in different education rates were significant (P0.05). Conclusion: Findings of this research can be useful for policymakers and managers to investigate environmental justice especially in mega cities.